Consentimento informado durante a pandemia de coronavírus: as decisões do Supremo Tribunal Federal sobre a vacinação obrigatória da população - Taborda, Marlon Adriano Balbon (2024)
The dissertation analyzes informed consent during the coronavirus pandemic, especially the decision of the Supreme Federal Court in the judgment of Direct Actions of Constitutionality 6,586 and 6,587. The problem to be solved is: to what extent did the STF's decision to authorize mandatory vaccination of the population against the coronavirus violate citizens' right to informed consent? Informed consent defends the freedom, autonomy and self-determination of citizens, giving them the right to refuse interventions in their bodies, although some theories argue that, in the name of collective interests - such as public health - vaccination may be mandatory. During the coronavirus pandemic, mandatory vaccination of the population was authorized in Brazil through Law 13,979/2020 (Quarantine Law). Many citizens were against this law, until the matter was judged by the Federal Supreme Court (STF) in Direct Actions of Constitutionality 6,586 and 6,587 - all ministers, with the notable exception of Nunes Marques, voted in favor of mandatory vaccination. It is concluded that the STF's decision in ADINS 6,586 and 6,587 violated, at least partially, the informed consent, since the mandatory vaccination of the population violated the freedom, autonomy and self-determination of Brazilian citizens who were forced to be vaccinated, especially due to the fact that they perform certain professional activities. The mandatory vaccination, despite being authorized by the STF, in the name of public health, violated the fundamental rights of citizens who did not agree to be vaccinated against the coronavirus and who feared the side effects of the vaccines. The 1988 Federal Constitution at no time expressly authorizes the restriction of fundamental rights in times of pandemic, and this restriction is not provided for in international documents such as the Universal Declaration of Human Rights or in classic Bioethics documents, such as the Nuremberg Code. The dissertation follows the inductive method and was developed in the research line "Social Relations and Dimensions of Power", of the Postgraduate Program in Law of the University of Passo Fundo. The main source of research is bibliographical and documentary sources, with the use of recent journalistic sources.